Static solid cooling (SSC) method for directional solidification and single crystal production: A CAFE simulation approach - Ahmad Saadati; Mehdi Malekan (Journal of Materials Research and Technology, 2024)
This article presents a novel directional solidification (DS) technique called static solid cooling (SSC), which has been characterized and compared to the conventional high rate solidification (HRS) method using finite element simulation and a coupled three-dimensional (3D) cellular automaton finite element (CAFE) method. The SSC technique uses alternative heat conductor and insulation layers to provide DS conditions. Simulation results show that the SSC method provides a higher cooling rate, temperature gradient, and velocity of the solidification front compared to the HRS method. Moreover, due to its higher heat dissipation ability, the SSC method produces a convex shape in the solidification front, which is crucial for the production of defect-free single crystal blades. According to the simulation model, the HRS method can produce a defect-free single crystal structure up to a withdrawal rate of 3 mm/min, whereas, the SSC method can maintain a single crystal structure without any stray grain defects up to a withdrawal rate of 6 mm/min. These findings demonstrate the effectiveness of the novel SSC technique over the conventional HRS method in producing high-quality single crystal structures. The proposed method could have significant implications for industries such as aerospace and energy that require high-performance materials with superior mechanical properties at elevated temperatures.